Are parents' knowledge and practice regarding immunization related to pediatrics' immunization compliance? a mixed method study - Al-lela, Omer Qutaiba; Bahari, Mohd Baidi; Al-Qazaz, Harith Khalid; Salih, Muhannad RM; Jamshed, Shazia Qasim; Elkalmi, Ramadan Mohamed Mahmod (BioMed Central Ltd, 2014)
Background Immunization rate is one of the best public health outcome and service indicators of the last 100 years. Parental decisions regarding immunization are very important to improve immunization rate. The aim of this study was to evaluate the correlation between parental knowledge-practices (KP) and children's immunization completeness.